Metrics evaluation for context-aware computing - Mantoro, Teddy (ACM New York, NY, USA, 2009)
This paper proposed a software product quality metrics for Context-aware Computing, based on Boehm Model, McCall Model and ISO/IEC 9126. This new evaluation metrics are based on the combinations of two aspects of the evaluation process, which are the technological and the social aspects and two dimensions of the core content, which are the user and environment dimensions. The evaluations of our experimental works based on the evaluation metrics are also presented.